Novel CD123 polyaptamer hydrogel edited by Cas9/sgRNA for AML-targeted therapy - Haibin Wu; Liyu Zhang; Zeen Zhu; Chenxi Ding; Shengquan Chen; Ruiping Liu; Huafeng Fan; Yang Chen; Hui Li (Taylor & Francis Group, 2021)
CD123 targeting molecules have been widely applied in acute myelocytic leukemia (AML) therapeutics. Although antibodies have been more widely used as targeting molecules, aptamer have unique advantages for CD123 targeting therapy. In this study, we constructed an aptamer hydrogel termed as SSFH which could be precisely cut by Cas9/sgRNA for programmed SS30 release. To construct hydrogel, rolling-circle amplification (RCA) was used to generate hydrogel containing CD123 aptamer SS30 and sgRNA-targeting sequence. After incubation with Cas9/sgRNA, SSFH could lose its gel property and liberated the SS30 aptamer sequence, and released SS30 has been confirmed by gel electrophoresis. In addition, SS30 released from SSFH could inhibit cell proliferation and induce cell apoptosis in vitro. Moreover, SSFH could prolong survival rate and inhibit tumor growth via JAK2/STAT5 signaling pathway in vivo. Additionally, molecular imaging revealed SSFH co-injected with Cas9/sgRNA remained at the injection site longer than free aptamer. Furthermore, once the levels of cytokines were increasing, the complementary sequences of aptamers injection could neutralize SS30 and relieve side effect immediately. This study suggested that CD123 aptamer hydrogel SSFH and Cas9/sgRNA system has strong potential for CD123-positive AML anticancer therapy.